Bytový dům - Murínová, Bohuslava (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Předmětem téhle bakalářské práce je vypracování projektové dokumentace pro bytový dům. Pozemek je rovinatý a nachází se v Novém Boru. Objekt má čtyři nadzemní podlaží a jedno podzemní podlaží. Střecha je řešena jako zelená se sklonem 2,62 %. Stavba je řešena jako zděná z pórobetonových tvárnic YTONG s monolitickými stropy. Všechny tepelně izolační produkty jsou od společnosti Isover. Výkresová dokumentace byla prováděna v počítačovém programu Allplan. Součástí dokumentace je požární, akustické, osvětlovací a tepelně technické řešení.

The subject of this bachelor thesis is to elaborate project documentation for a residential building. It is located in Nový Bor. Construction site has a relatively flat profile. It has four above ground floors and one underground floor. Roof is flat green roof with a slope of 2,62 %. The whole construction is from reinforced concreate and mansonry with main use on construction materials from the company YTONG. The insulation materials are all from the company ISOVER. The drawing documentation necessary for the realization of this residential building was elaborated in Allplan computer program. Part of the work is fire, acoustic and thermal-technical solution.
Apartment building
Keywords: Bytový dům; Ytong; Isover; železobeton; zděné konstrukce; zelené ploché střechy; Allplan; suterén; Apartment building; Ytong; Isover; reinforced concreate; masonry construction; flat green roof; Allplan; basement